Toward the simultaneous detection of multiple diseases with a highly cost-effective cell-free DNA methylome test - Weihua Zeng; Chun-Chi Liu; Shuo Li; Yonggang Zhou; Mary L. Stackpole; Ying Xiao; Ran Hu; Caitlin Tang; Qiao Liu; Wanwen Zeng; Angela Yeh; Andrew Melehy; et al. (Proceedings of the National Academy of Sciences, 2026)
Plasma cell-free DNA (cfDNA), originating from multiple organs, holds significant potential for noninvasive diagnostics and prognostics. Current cfDNA methylation assays primarily focus on single clinical indications by targeting specific genomic loci. In contrast, comprehensive profiling of cfDNA methylome can enable simultaneous detection of multiple diseases by capturing organ-specific methylation signatures, thereby offering a holistic view of health, when disease etiology is unclear or when conventional biochemical diagnostics are unavailable. However, deep sequencing required for sensitive detection of methylation abnormalities remains prohibitively expensive, limiting widespread clinical use. To overcome this barrier, we developed MethylScan , a highly cost-effective approach for cfDNA methylome sequencing. We demonstrated its broad clinical utility in a cohort of 1,061 individuals across diverse applications, including multicancer detection in general population, liver cancer surveillance in high-risk individuals, liver disease classification, identification of organ abnormalities, and race prediction from cfDNA. In multicancer detection (liver, lung, ovarian, and stomach cancers), MethylScan achieved an area under the receiver operating characteristic curve (AUROC) of 0.938 (95% CI: 0.920 to 0.954), with a sensitivity of 63.3% (95% CI: 58.9 to 67.9%) at 98.0% specificity for all cancer stages. For early-stage cancers, the AUROC was 0.916 (95% CI: 0.890 to 0.940), with 55.3% sensitivity (95% CI: 49.1 to 62.1%) at the same specificity. In liver cancer surveillance, MethylScan achieved an AUROC of 0.927 (95% CI: 0.889 to 0.959), with 79.6% sensitivity (95% CI: 70.6 to 87.8%) at 90.4% specificity. The assay also demonstrated strong performance in additional diagnostic tasks, supporting its potential as a versatile platform for comprehensive cfDNA-based health monitoring.